Impact of apixaban treatment discontinuation on the risk of hospitalization among patients with nonvalvular atrial fibrillation and COVID-19. (2nd November 2022) - Deitelzweig, Steven; Zhu, Julia; Jiang, Jenny; Luo, Xuemei; Keshishian, Allison; Ferri, Mauricio; Rosenblatt, Lisa; Schuler, Patricia; Gutierrez, Cynthia; Dhamane, Amol D.
Abstract: Introduction: This study evaluated the risk of hospitalization among nonvalvular atrial fibrillation (NVAF) patients with an outpatient COVID-19 diagnosis who discontinued vs continued apixaban treatment. Methods: Adult patients with NVAF with an apixaban prescription prior to an outpatient COVID-19 diagnosis were identified from Optum Clinformatics claims database (1 April 2020–31 March 2021). Continuers were those who continued apixaban as of the index date (date of initial outpatient COVID-19 diagnosis) and discontinuers were those who had the last day of apixaban supply on or before index. Patients were followed from COVID-19 diagnosis to change of continuation/discontinuation status, switch, death, end of continuous coverage or study end, whichever occurred first. Inverse probability treatment weighting (IPTW) was performed to balance cohorts. Cox proportional hazard models were used to compare the risk of all-cause hospitalization and hospitalization for ischemic stroke (IS), venous thromboembolism (VTE), myocardial infarction (MI), bleeding and mortality. Results: A total of 7869 apixaban patients with COVID-19 were included: 6676 continuers (84.8%) and 1193 discontinuers (15.2%). Compared with continuers, discontinuers had a higher risk of all-cause hospitalization (hazard ratio [HR]: 1.23; 95% confidence interval [CI]: 1.08–1.40), IS (HR: 2.00; 95% CI: 1.03–3.87), VTE (HR: 2.37; 95% CI: 1.06–5.27) and mortality (HR: 2.28; 95% CI: 1.85–2.80). There were no significant differences in the risk of MI (HR: 1.01; 95% CI: 0.54–1.90) or bleeding-related hospitalization (HR: 1.13; 95% CI: 0.73–1.76). Conclusion: NVAF patients with COVID-19 who discontinued apixaban had a higher risk of hospitalization and thrombotic events vs those who continued apixaban, with no significant difference in bleeding-related hospitalization.